Pharmacological effects of nicotine salts on dopamine release in the nucleus accumbens - Li, Xiaonan; Lu, Lehua; He, Ying; Zhang, Hui; Zhang, Yihui; Sheng, Huaquan; Chen, Ming; Ru, Jiexiong; Gao, Yihan (Frontiers in Pharmacology, 2023)
With the growing number of individuals regularly using e-cigarettes, it has become increasingly important to understand the psychobiological effects of nicotine salts. Nicotine increases the release of dopamine (DA) into the nucleus accumbens (NAc), causing feelings of satisfaction. However, the differences in the DA-increasing effects of different nicotine salts have not been reported. In this study, we used a G protein-coupled receptor-activated DA fluorescent probe (GRABDA1m) and optical fiber photometric recording equipment to monitor the dynamic changes and kinetics of DA release in the NAc of mice exposed to different e-cigarette aerosols, including nicotine, nicotine benzoate, nicotine tartrate, nicotine lactate, nicotine levulinic acid, nicotine malate, and nicotine citrate. The results of this study were as follows: (1) Different types of nicotine salts could increase the release of DA in the NAc.